Comprehensive genome methylation and whole genome expression analysis in penile carcinoma: Uncovering new molecular markers - Kuasne, Hellen; Syllos Colus, Ilce Mara de; Hernandez-Vargas, Hector; Busso-Lopes, Ariane Fernanda; Barros-Filho, Mateus C.; Marchi, Fabio A.; Scapulatempo-Neto, Christovan; Faria, Eliney F.; Lopes, Ademar; Guimaraes, Gustavo C.; Herceg, Zdenko; Rogatto, Silvia Regina [UNESP] (Amer Assoc Cancer Research, 2014)
Background: Penile carcinoma (PeCa) is frequently associated with high morbidity rates. Unlikely of the vast majority of tumors, there is no molecular markers described that are able to assist in diagnosis and prognosis or with potential to be therapeutic targets in PeCa. Patients and methods: DNA methylation status (244K Human DNA Methylation Microarray platform, Agilent Technologies) and large-scale expression analysis (4x44K Whole Human Genome Microarray, Agilent Technologies) were performed in 35 and 37 PeCa, respectively. Quantitative bisulfite pyrosequencing (qBP) and RT-qPCR were used to validate the findings in 93 samples. HPV status was assessed using the Linear Array HPV Genotyping kit (Roche Molecular Diagnostics, CA, USA). Results: Methylome analysis revealed 171 hypermethylated and 449 hypomethylated CpGs sites and the transcriptome profiling showed 2986 down- and 2817 over-expressed genes. HPV positivity was found in 32.7% of the cases, mainly the HPV16. The integrative analysis in 32 PeCa revealed a panel of 96 genes with inverse correlation between methylation and gene expression levels. The CpG hypermetlylation and gene downexpression, was confirmed for TWIST1, RSOP2, SOX3, SOX17, CD133, OTX2, HOXA3 and MEIS. In addition, BIRC5, DNMT1 and DNMT3B presented low levels of methylation and overexpression. The comparison of the results with clinical findings revealed that LIN28A, NKX2.2, NKX2.3, LHX5, BDNF, FOXA1 and CDX2 were associated with poor prognosis features. Conclusion: Putative prognostic markers were detected revealing that DNA methylation modulates the expression of several genes in PeCa. These data may prove instrumental for biomarker discovery in clinics and molecular epidemiology of PeCa.